Design and characterization of a floating model membrane platform for biosensor applications - Yao, Bingxin (2012)
Supported lipid bilayers are widely used model membrane mimics in biosensor applications, whose properties can be adjusted to suit specific interests. Over the past years, one of the major challenges in this area is to increase the hydration layer thickness in between the supporting substrate and the lipid bilayer so as to enable the incorporation of transmembrane proteins and related studies. In this work, we present a noble method which managed to increase the hydration layer thickness via the adjustment of buffer pH. By increasing the buffer pH in a gentle fashion, ―floatation‖ of the formed lipid bilayers was achieved on both silicon oxide and titanium oxide substrates, as confirmed by the Quartz Crystal Microbalance with Dissipation Monitoring method. Further physical examination of the floating lipid bilayer via Fluorescence Recovery after Photobleaching also demonstrated enhanced lipid fluidity as pH went up. The newly developed floating model membrane system has promising potential in advanced biosensor applications.